2012
DOI: 10.1016/j.electacta.2012.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behaviour of myoglobin at an array of microscopic liquid–liquid interfaces

Abstract: Electrochemistry at liquid-liquid interfaces, or at interfaces between two immiscible electrolyte solutions (ITIES), provides a basis for the non-redox detection of biological molecules, based on iontransfer or adsorption processes. The electroactivity of myoglobin at an array of micron-sized liquidorganogel interfaces was investigated. The µITIES array was patterned with a silicon membrane consisting of an array of eight pores with radii of ~12.8 µm and a pore to pore separation of ~400 µm.Using cyclic voltam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 57 publications
2
59
1
1
Order By: Relevance
“…A recent study 64 of the behaviour of myoglobin at a µITIES array indicated a similar detection capability as seen for HEWL and insulin, namely the achievement of 1 µM detection. Additionally, it was found that a single CV cycle resulted in the adsorption and desorption of an interfacial layer of the protein consistent with a coverage of 10-50 pmol cm -2 , assuming that the protein was fully protonated when in aqueous acidic (pH 2)…”
Section: Protein Detection At the µItiesmentioning
confidence: 92%
“…A recent study 64 of the behaviour of myoglobin at a µITIES array indicated a similar detection capability as seen for HEWL and insulin, namely the achievement of 1 µM detection. Additionally, it was found that a single CV cycle resulted in the adsorption and desorption of an interfacial layer of the protein consistent with a coverage of 10-50 pmol cm -2 , assuming that the protein was fully protonated when in aqueous acidic (pH 2)…”
Section: Protein Detection At the µItiesmentioning
confidence: 92%
“…The peak-shaped response on the reverse sweep is quite different to that in Figure 1 A and is consistent with thin-film or desorption behavior. [12,20] Figure 1 C shows that the ion-transfer current waves produced from a mixture of TEA + and amylin are still clearly identifiable as individual processes, indicating that there is no interference in the TEA + transfer process by the polypeptide in solution (and vice versa). However, there are no pre or post peaks on the forward scan voltammogram, which are usually present when products or reactants adsorb at an electrified interface.…”
Section: Resultsmentioning
confidence: 99%
“…10,[15][16][17][18][19][20][21][22] Both ohmic drop and capacitive currents are dramatically diminished utilizing these ultra-small liquidliquid interfaces. For instance, nanopipets, micro and nanofabrication are used to develop massive sensor arrays.…”
Section: -14mentioning
confidence: 99%